Pengaruh Motivasi Belajar dan Minat Belajar Terhadap Hasil Belajar Matematika Pada Peserta Didik Kelas IV - Choliza, Inneke Nur; Yulianto, Sigit (Paedagogie, 2026)
This study looks at how fourth-grade pupils at Jetakwanger Elementary School in Blora Regency learn mathematics in relation to their motivation and interest in the subject. All fourth-grade children served as the sample for this study, which employed a quantitative correlational design with saturation sampling. Students' math performance was noted, and data was gathered using a questionnaire that assessed learning motivation and interest. Descriptive and inferential statistical techniques were used to assess the data in order to spread the hypothesis that was provided. The findings demonstrated that students' drive to study had a substantial impact on their learning achievements in mathematics. Learning interest also has a big impact on math achievement. Additionally, learning motivation and curiosity have a major impact on students' learning results in mathematics. This study came to the conclusion that raising student interest and engagement is necessary to improve math skills in primary schools. Keywords: learning motivation, learning interest, mathematics learning outcomes, elementary school